A risk assessment of the food supply chain: vulnerability against terrorist or criminal contamination. (19th September 2011) - Alvarez, M.J.; Alvarez, A.; De Giacomo, M.; De Maggio, M.C.; Onori, R.; Oses, A.; Sarriegi, J.M.; Setola, R.; Trombetta, M.
The food supply chain has been recognised by the USA and the EU as a critical infrastructure, and it should be considered a target for possible terrorist attacks. In this paper, we present a methodological approach developed within the EU project SecuFood to evaluate the risk associated with this threat. The usefulness of the approach is related to the improvement of the analysis of food supply chain risk in terms of the potential threats, the vulnerability of the system, and the effectiveness of counter measures. The followed approach is based on identifying biological and chemical hazards, analysing those biological and chemical agents, and determining the risk level they present in the main phases of the food supply chain. We consider the feasibility of an attack (what we call likelihood), taking into account the accessibility and manageability of the contamination agents, the vulnerability of the supply chain for specific products, and the possible adverse consequences.